Strategic Orientations to Strengthen Policymaking: Study of Small-Scale Cassava-Based Agroindustry in Central Java, Indonesia - Kusnandar Kusnandar; Nuning Setyowati; Wiwit Rahayu (Universitas Muhammadiyah Yogyakarta, 2023)
The cassava agroindustry is an essential part of the food sub-sector, and as it provides economic benefits for business actors from upstream to downstream. The development of the industry has been focused on aspects of cultivation, whereas the aspects of processing, marketing, management, and business innovation also need support. This study aims to formulate strategic orientations of SMEs in developing cassava-based agroindustry. This exploratory study was conducted on SMEs in the agroindustry with products made from cassava. A total of 115 SMEs in Central Java Province were taken as samples using stratified random sampling. Factor analysis was performed with the Principle Component Analysis (PCA). The strategic orientations covered product focus and short-term orientation to survive; market knowledge and flexibility; long-term orientation for market penetration or development; product development innovation to create differentiation; and reactive strategy orientation for stability. These five aspects should be considered to win the competition, build a competitive advantage, and face changes in the business environment. However, implementing them required the commitment of cassava-based SMEs, government support, and the development of collaboration with larger industries. Thus, the strategic orientations could be applied as a regional policy to improve the business performance in the cassava agroindustry in Central Java.